2016
DOI: 10.1007/s11914-016-0314-3
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Level Mechanical Properties of Bone Contributing to Fracture Risk

Abstract: Tissue-level mechanical properties characterize mechanical behavior independently of microscopic porosity. Specifically, quasi-static nanoindentation provides measurements of modulus (stiffness) and hardness (resistance to yielding) of tissue at the length scale of the lamella, while dynamic nanoindentation assesses time-dependent behavior in the form of storage modulus (stiffness), loss modulus (dampening), and loss factor (ratio of the two). While these properties are useful in establishing how a gene, signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 98 publications
(103 reference statements)
3
30
1
Order By: Relevance
“…All other techniques from X‐ray imaging and ultrasound to magnetic resonance imaging with finite element analysis provide surrogates of fracture resistance. While these surrogates related to bone mass, cortical structure, trabecular architecture, structural strength, and mineral density are significantly different between osteoporotic and otherwise healthy bone, they do not unequivocally predict fracture risk . IMI may help with fracture risk assessment as it provides a unique tissue characteristic related to the mechanical resistance of cortical bone to high‐rate indentation.…”
Section: Discussionmentioning
confidence: 99%
“…All other techniques from X‐ray imaging and ultrasound to magnetic resonance imaging with finite element analysis provide surrogates of fracture resistance. While these surrogates related to bone mass, cortical structure, trabecular architecture, structural strength, and mineral density are significantly different between osteoporotic and otherwise healthy bone, they do not unequivocally predict fracture risk . IMI may help with fracture risk assessment as it provides a unique tissue characteristic related to the mechanical resistance of cortical bone to high‐rate indentation.…”
Section: Discussionmentioning
confidence: 99%
“…In case-control studies to identify significant associations between tissue composition by spectroscopy and fracture risk, a clear understanding of how spectroscopic measurements relate to fracture resistance has also not yet emerged 19,20 . As an example, one study reported higher carbonate-to-phosphate ratio, as determined by RS, in the cortex of iliac crest biopsies from fracture cases compared to non-fracture controls (age-matched women) 21 , while in another iliac biopsy study matching both age and areal bone mineral density between the cases, the carbonate-to-phosphate ratio of the cortex, as determined by Fourier transform infrared (FTIR) imaging, was significantly lower for women with fractures than for women without fractures 22 .…”
Section: Introductionmentioning
confidence: 99%
“…However, AGEs were shown not to affect the stiffness of the bone at the apparent-level although it increased the stiffness of individual trabeculae (Tang et al, 2007). Bone tissue mechanical properties, however, are highly related to tissue age instead of the donor age (Nyman et al, 2016;Ojanen et al, 2015). Using finite element (FE) modeling, material properties have been incorporated to 3D bone structure, as imaged using µCT, to predict apparent-level mechanical response of bone (Chen et al, 2017;Hambli, 2013;Müller and Rüegsegger, 1995;Sandino et al, 2015).…”
Section: Introductionmentioning
confidence: 99%